A broad-band X-ray view of the Warm Absorber in radio-quiet quasar MR2251-178 - Gofford, J; Reeves, J; Turner, T; Tombesi, F; Braito, V; Porquet, D; Miller, L; Kraemer, S; Fukazawa, Y (2011)
We present the analysis of a new broad-band X-ray spectrum (0.6-180.0 keV) of the radio-quiet quasar MR 2251-178 which uses data obtained with both Suzaku and the Swift/BAT. In accordance with previous observations, we find that the general continuum can be well described by a power-law with Γ=1.6 and an apparent soft-excess below 1 keV. Warm absorption is clearly present and absorption lines due to the Fe UTA, Fe L (Fe XXIII-XXIV), S XV and S XVI are detected below 3 keV. At higher energies, Fe K absorption from Fe XXV-XXVI is detected and a relatively weak (EW=25[+12,-8] eV) narrow Fe Kα emission line is observed at E=6.44±0.04 keV. The Fe Kα emission is well modelled by the presence of a mildly ionised (ξ≤30) reflection component with a low reflection fraction (R<0.2). At least 5 ionised absorption components with 10^{20} ≤ N_H ≤ 10^{23} cm^{-2} and 0 ≤ log(ξ)/erg cm s^{-1} ≤ 4 are required to achieve an adequate spectral fit. Alternatively, we show that the continuum can also be fit if a Γ~2.0 power-law is absorbed by a column of N_H~10^{23} cm^{-2} which covers ~30% of the source flux. Independent of which continuum model is adopted, the Fe L and Fe XXV Heα lines are described by a single absorber outflowing with v_out~0.14 c. Such an outflow/disk wind is likely to be substantially clumped (b~10^{-3}) in order to not vastly exceed the likely accretion rate of the source.